A Study on Job Satisfaction and Employee Effectiveness with Special Reference to Hospitality Industry - Jain, Divya (SFIMAR Research Review, 2015)
An optimistic&enthusiastic work force makes a successful organization. The employees' attitude towards the work they do plays an important role in how they perform. A general premise is that a satisfied worker is a productive worker. Complete satisfaction will create a positive working environment in the organization & will enable the employees to work harder towards attaining organizational goals. Thus, Job Satisfaction & productivity have a strong connection in the corporate world. The objective of the present study is to investigate the relation between job satisfaction (herein referred as JS) & employee effectiveness within the context of hospitality industry. The research will also focus upon assessing the impact of the sub scales of JS on effectiveness. Further, an attempt is made to find out if productivity varies between the levels of management. Minnesota Satisfaction Scale was used to assess JS level of employees. Correlation, regression, ANNOVA statistical tools were used to test hypothesis. Results revealed a significant relationship between the two variables. Intrinsic satisfaction was proving to be the most significant predictor of employee effectiveness.